"Non-traditional" stable isotopes applied to the study of trace metal contaminants in anthropized marine environments. (February 2022) - Araújo, Daniel F.; Knoery, Joël; Briant, Nicolas; Vigier, Nathalie; Ponzevera, Emmanuel
Abstract: The advent of Multicollector ICP-MS inaugurated the analysis of new metal isotope systems, the so-called "non-traditional" isotopes. They are now available tools to study geochemical and ecotoxicological aspects of marine metal contamination and hence, to push the frontiers of our knowledge. However, such applications are still in their infancy, and an accessible state-of-the-art describing main applications, obstacles, gaps, and directions for further development was missing from the literature. This paper fills this gap and aims to encourage the marine scientific community to explore the contributions of this newly available information for the fields of chemical risk assessment, biomonitoring, and trophic transfer of metal contaminants. In the current "Anthropocene" epoch, metal contamination will continue to threaten marine aquatic ecosystems, and "non-traditional" isotopes can be a valuable tool to detect human-induced changes across time-space involving metal contaminants, and their interaction with marine biota. Graphical abstract: Unlabelled Image Highlights: In the current "Anthropocene" epoch, trace metal contamination will threaten marine aquatic ecosystems. "Non-traditional" metal stable isotopes empower marine scientists to detect man-induced biogeochemical changes. They provide geochemical information about the sources and dispersion mechanisms of anthropogenic metals. They help understand bioaccumulation mechanisms, trophic transfers, and intracellular interactions. Marine scientific community can use this new isotope information for chemical risk assessment and biomonitoring.